Ação política, transformação social e reconstrução de identidades: um olhar a partir do feminismo para a militância das mulheres rurais nos movimentos sociais - Cruz, Elizabeth Ferreira (2008)
The present research's main objective was to identify and analyze the transformations that occurred in the dimensions of the identity and the subject position of rural women that exercise political militancy in social movements in rural Ceará. It sought also to apprehend if the linking or proximity with feminism, as it ideology/vision of the world, theory or social movement, it constitutes a differential for the change of position of the subject of militant women, contributing so that these women can be more autonomous, so much in the movements of which they are a part, as in their routine life in the scope of the familiar relations. The analysis concentrates itself in the experiences of militant women of three social movements: Movement of Rural Working Women of the Northeast – MMTR/NE, Movement of Rural Workers Without Land – MST and Union Movement of Rural Workers – MSTTR. It analyzes also the experiences of rural women that aren't militants in social movements of form to be able to identify and complicate differences and resemblances between the two groups, establishing or not if the political militancy provokes significant transformations in the dimensions of the identity and in the routine practices of the militant women. The key concepts in this study are: identity, subject, social transformation and militancy. This reflection is based on epistemological, theoretic and methodological principles of Feminist Theories e Marxism. In able to better apprehend the object of study, a methodological procedure to qualitative research was adopted, in a feminist approach, reaping the empirical facts through individual and collective interviews (focal group), participant observation, as well as the analysis of documents. The conclusions indicate that the political militancy in social movements, even if they are not sufficient to constitute the women as full subjects of themselves, it contributes in a significant form so that these women act in their own lives, political and private, with more autonomy than those that are not militants in social movements. The militancy enables bigger knowledge, bigger access to the information and the experience in a political-public world that creates conditions for the exercise of a citizen practice, such as proposition and claim of rights. There are significant differences between the women who are active militants and those that are not, specifically, in their vision about class and gender domination trials in the world. Even if there are resemblances in the perceptions about the transformations occurred in the rural environment, the militant women show a posture more critical about those transformations, some identifying in them contradictions. Also, it was possible to identify that between the militant women there is a perception more critical of the uneven relations between women and men and of the present patriarchal culture in out society, especially, those that have some straight or indirect bond with the feminism. Between these, it was established a trial of change in the relations of kind in the family scope, including a bigger division of the housework.